Impactos socioambientais da usina hidrelétrica Dona Francisca - Prates, Camila Dellagnese (2011)
This present work has as main objective to engage in the environmental and social im'pacts analysis caused bu the construction of the Dona Francisca hidroelectric power plant situated in the central region of the Rio Grande do Sul state, Brazil. Initially, the work is based on reports of social impacts of the Dona Francisca hidroelectric power plant, to comprehend how the individuals that had chosen the rellocation based on great lot amount are studied and understood. Complementing this first analysis and the bibliographical review of authors that study general sociology, as Antony Giddens, Ignacy Sachs, Ulrich Beck and Amartya Sen to complement the same theories. These authors will help me to scope the tools used to analyse the social and environmental studies by stugying the effected individuals. The rationality was captured based on a structured questionário containing closed and opened questions. The closed questions part consisted in a description of the structual issue and social phenomenon that surroud the ressetled and its community. The opened questions explored issues that demanded a recall from the ressetlement, by considering the current social and economical life and also a projection of their future. The data showed that considering both closed and opened questions, it is clear some reflection points about the object. It was used the approach of Amartya Sen to make an analytical cleavage of the impacts in their lifes. The data demonstrated that in a general way, the individuals dont fit in the theory of human developing from Amartya Sen. Considering that, it is possible to comprehend that the ressetled individuals chase development trough the economical activities. The research demonstrates through epistemological data that it is necessessary to strengthen the social and environmental studies by using cases that exist already. These type of word would improve some solutions to those individuals.